Valʹter Benʹjamin i slabka mesiansʹka syla = Walter Benjamin and the Weak Messianic Power - Denysenko, Anatolij (Bogoslovs'ki rozdymi, 2021)
Walter Benjamin (1892-1940) was a German intellectual of Jewish descent, a well-known literary critic, philosopher, sociologist, translator and essayist, and a key figure in continental philosophy. His works on topics such as historical materialism, German idealism, and Jewish mysticism have had a marked influence on contemporary aesthetic theories and the development of Western Marxism, including the Frankfurt School of Critical Theory. These articles will focus on the analysis of the concept of messianism, which Benjamin develops in his work "On the concept of history" or "Theses on the philosophy of history" (1940). Messianism here is neither a theological dogma nor a modern figure of the utopian. Benjamin’s messianic time does not refer to the future, but to the urgency of the "now." The author contrasts the "weak messianic force" of the tradition of the oppressed, which demands the past with the realization of happiness and liberation in the present, and Jetztzeit - a model of messianic time, open and nonlinear time of rupture, based on modern (contemporary) forms of collective experience past and liberation memory (Eingedenken).